Acquired hemophilia A. Issue 1 (2nd January 2020) - Pandey, Yadav; Atwal, Dinesh; Konda, Manojna; Roy, Arya; Sasapu, Appalanaidu
Abstract: Acquired inhibitors of coagulation are a group of rare but potentially life-threatening blood disorders characterized by the presence of autoantibodies directed against clotting factor. Autoantibody against factor VIII is the most common form of clotting factor inhibitor, a condition also known as acquired hemophilia A. We present a clinical series of nine patients diagnosed and treated for acquired hemophilia A at our institution. Among these nine patients, there were five men and four women with a median age of 64 years. All patients presented with bleeding diathesis. Factor eight inhibitor bypassing agent and/or recombinant factor VIIa were predominantly used for control of active bleeding. For elimination of autoantibodies, either steroids alone or the combination of steroids with rituximab or oral cyclophosphamide was used. Despite aggressive measures, two of the patients had a poor outcome; seven of the nine patients (77%) had a good clinical outcome. Acquired hemophilia A should be strongly suspected in any patient presenting with bleeding and a prolonged activated partial thromboplastin time. Early initiation of factor bypassing agents such as activated prothrombin complex concentrates or recombinant factor VIIa, along with the use of immunosuppressive agents, can be lifesaving.